Myocardial Protection During Aortic Arch Repair in a Piglet Model: Beating Heart Technique Compared With Crystalloid Cardioplegia - Janssen, Carina; Kellermann, Stephanie; Münch, Frank; Purbojo, Ariawan; Cesnjevar, Robert; Rueffer, Andre (Annals of Thoracic Surgery, 2015)
Selective myocardial perfusion enables repair of congenital aortic arch obstruction without cardiac arrest. This study was inspired by the lack of prospective controlled studies of the beating heart (BH) technique compared with cold crystalloid cardioplegia (CC) regarding effects on myocardial performance, ischemic damage, and serum electrolyte levels.In a prospective study, 20 male piglets weighing 11.1 ± 1.3 kg were operated on using cardiopulmonary bypass (CPB) and underwent 60 minutes of aortic cross-clamping. According to prospective randomization, myocardial protection included either a BH modification with selective myocardial perfusion using an individual roller pump or CC. Hemodynamic performance was evaluated by a conductance catheter technique before and after CPB and calculated in relation to baseline levels. Laboratory analysis included blood levels of troponin T and serum electrolytes.Eighteen piglets entered analysis. There were significantly higher slopes of end-systolic pressure-volume relations (168% ± 92% versus 89% ± 16%; p = 0.046) and preload-recruitable stroke work (PRSW) (139% ± 37% versus 103% ± 31%; p = 0.040) in BH piglets compared with those who underwent CC. Laboratory analysis during reperfusion revealed higher levels of troponin T (1.31 ± 0.28 ng/mL versus 0.49 ± 0.17 ng/mL; p < 0.01) and sodium (131 ± 4 mmol/L versus 120 ± 8 mmol/L; p = 0.003) and lower levels of potassium (4.8 ± 0.4 mmol/L versus 6.4 ± 1.0 mmol/L; p = 0.001) with BH compared with CC, whereas no significant differences were calculated at the end of the experiment.The BH technique is associated with improved contractility compared with standard CC. There is comparable ischemic damage in both groups, with an earlier rise in blood levels of troponin T after BH and more fluctuation of serum electrolytes with CC. Evidence of ischemic changes should dissuade one from using the BH technique imprudently.
EVALuna2:25809